Production components, grain yield and water use efficiency of irrigated cowpea - Irene Filho, João; Andrade Júnior, Aderson Soares de; Ferreira, José Orlando Piauilino; Blanco, Flávio Favaro; Cardoso, Milton José (Comunicata Scientiae, 2018)
Cowpea cultivars, which are indicated for irrigated cropping, are recommended without proper assessment of their productive potential and water use efficiency in response to water regimes in the soil from different production environments. The aim of this study was to evaluate the production components, the yield performance and the efficiency of water use of cowpea cultivars in response to the application of irrigation depths under the soil and climate conditions of Bom Jesus, PI. The experiment was performed from June to August 2011 in a soil classified as sandy-textured Fluvic Neosol. The study was conducted in a randomized blocks design, with four replicates. The treatments were arranged in subdivided plots (irrigation depths in plots and cultivars in subplots). The cultivars BRS Aracê (semi-prostrate) and BRS Tumucumaque (semi-erect) were submitted to five irrigation depths (108.2, 214.7, 287.9, 426.1 and 527.7 mm). The number of pods per plant and the weight of one hundred grains are the main components related to grain yield. The cultivar BRS Tumucumaque presented a better yield performance (1697.2 kg ha-1) than the cultivar BRS Aracê (1233.8 kg ha-1), with the application of the irrigation depths of 527.7 and 522.4 mm, respectively. The highest water use efficiency (0.420 kg m-3) is obtained with the application of the irrigation depth of 108.2 mm in both cultivars.